Mesoscale blood cell sedimentation for processing millilitre sample volumes1. Issue 16 (21st August 2015) - Galligan, C.; Nichols, J.; Kvam, E.; Spooner, P.; Gettings, R.; Zhu, L.; Puleo, C. M.
<x xml:space="preserve">Abstract</x> We demonstrate the efficient separation of blood cells from millilitre volumes of whole blood in minutes using a simple gravity sedimentation device.